Hedging in Political Discourse: Evidence from the Speeches of King Abdullah II of Jordan - Rabab’ah Ghaleb; Abu Rumman Ronza (Prague Journal of English Studies, 2015)
This paper reports on the findings of a study that aimed to identify the linguistic items which act as hedges in the speeches of King Abdullah II of Jordan, as well as to examine the pragmatic functions of these devices. Twenty-five political speeches of King Abdullah II, randomly selected from the official website of King Abdullah (see Appendix), were analyzed adopting Salager-Meyer’s (1994) taxonomy. The study revealed that the most frequently used hedging device in King Abdullah’s speech is modal auxiliaries, and the most frequently used hedging device subcategory is the modal auxiliary “can”. The findings suggest that these hedging devices fulfil several pragmatic functions. These findings contribute to understanding that speaking a second language (Arabic, in the case of King Abdullah II) neither affects the types of hedging devices nor the functions these devices perform. Moreover, contrary to scientific discourse (e.g., medicine), the research concludes that political discourse as a non-scientific genre resorts to hedging devices to express indirectness, politeness, lack of commitment and probability.